2018
DOI: 10.1016/j.psyneuen.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic stress and accelerated DNA methylation age: A meta-analysis

Abstract: Results suggest that traumatic stress is associated with advanced epigenetic age and raise the possibility that cells integral to immune system maintenance and responsivity play a role in this. This study highlights the need for additional research into the biological mechanisms linking traumatic stress to accelerated DNA methylation age and the importance of furthering our understanding of the neurobiological and health consequences of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
157
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 201 publications
(179 citation statements)
references
References 77 publications
(105 reference statements)
20
157
2
Order By: Relevance
“…Since cumulative life stress has been shown to be strongly predictive of accelerated epigenetic aging 132 , the persistent symptoms and residual effects of PTSD may themselves be chronic stressors that promote accelerated epigenetic aging. This is in contrast to current PTSD diagnosis or severity, which has not been found to associate with accelerated epigenetic aging 130 . As a matter of fact, a longitudinal study of military personnel reported an apparent reversal of epigenetic aging during development of PTSD symptoms 133 , which suggests an initial attempt at compensation before loss of control and accelerated epigenetic aging.…”
Section: Epigenetic Effects Of Stress/trauma Response In the Brain Ancontrasting
confidence: 61%
See 1 more Smart Citation
“…Since cumulative life stress has been shown to be strongly predictive of accelerated epigenetic aging 132 , the persistent symptoms and residual effects of PTSD may themselves be chronic stressors that promote accelerated epigenetic aging. This is in contrast to current PTSD diagnosis or severity, which has not been found to associate with accelerated epigenetic aging 130 . As a matter of fact, a longitudinal study of military personnel reported an apparent reversal of epigenetic aging during development of PTSD symptoms 133 , which suggests an initial attempt at compensation before loss of control and accelerated epigenetic aging.…”
Section: Epigenetic Effects Of Stress/trauma Response In the Brain Ancontrasting
confidence: 61%
“…In fact, lifetime PTSD severity has been found to be associated with accelerated aging 129,130 based on one DNA methylation-based calculation of cellular age 131 , as well as reduced neural integrity (in the genu of the corpus callosum), as indexed by DTI 129 . Since cumulative life stress has been shown to be strongly predictive of accelerated epigenetic aging 132 , the persistent symptoms and residual effects of PTSD may themselves be chronic stressors that promote accelerated epigenetic aging.…”
Section: Epigenetic Effects Of Stress/trauma Response In the Brain Anmentioning
confidence: 99%
“…Given these mixed patterns of results across studies and the variability in findings across the two algorithms, Wolf et al [62] conducted a meta-analysis of over 2000 subjects and nine cohorts contributing to the Psychiatric Genomics Consortium PTSD Epigenetics Workgroup [63] and found that lifetime PTSD symptom severity and childhood trauma (when assessed with a particularly sensitive self-report instrument) were associated with accelerated Hannum DNAm age. No trauma or PTSD-related effects emerged for the Horvath index.…”
Section: Traumatic Stress and Accelerated Cellular Aging In The Epi/gmentioning
confidence: 99%
“…Specifically, robust associations between estimated white blood cell counts and accelerated DNAm age have emerged across studies, such as a negative relationship between CD4 T-cell counts and accelerated Hannum DNAm [55, 60••, 6162]. There is also preliminary evidence for an association between Horvath epigenetic age acceleration (adjusted for white blood cell counts) and increased C-reactive protein as well as between Hannum epigenetic age acceleration (in an index combined with white blood cell counts, see below) and increased C-reactive protein [78].…”
Section: Potential Mechanisms Linking Traumatic Stress To Acceleratedmentioning
confidence: 99%
“…In addition to relationships between EAA and growth under energetic constraint, it is also potentially important to understand how concurrent exposure to psychosocial and energetic stressors relates to children's EAA. Multiple studies have shown that individuals experiencing psychosocial adversity prior to adulthood exhibit greater EAA, and children's family environments may play a role in shaping these effects (Brody, Miller, Yu, Beach, & Chen, ; Javed, Chen, Lin, & Liang, ; Jovanovic et al, ; Lawn et al, ; Sumner, Colich, Uddin, Armstrong, & McLaughlin, ; Wolf et al, ). For example, research among African‐American children found that supportive family contexts were protective for children against the effects of racial discrimination on EAA (Brody, Yu, Chen, Beach, & Miller, ).…”
Section: Introductionmentioning
confidence: 99%